1988
DOI: 10.1252/jcej.21.522
|View full text |Cite
|
Sign up to set email alerts
|

Wall-to-liquid mass transfer in packed and fluidized beds with gas-liquid concurrent upflow.

Abstract: The wall-to-liquid mass transfer coefficient, kw, was measured for both surfaces of a coaxially immersed tube and a column wall in packed and fluidized bed systems with gas-liquid concurrent up flow. Supplementary measurements of kw were carried out in openpipe liquid flow, gas-liquid two-phase up flow and packed and fluidized beds with single liquid flow. The value of kwin the three-phase fluidized bed increased with increasing gas flow rate, deviating from the value in the liquid-solid fluidized bed and appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 4 publications
(4 reference statements)
5
16
0
Order By: Relevance
“…It is shown that the mass transfer correlation proposed by Yasunishi et al [26] is pretty close to the present correlation for the heat transfer, Eq. (12), which, in turn, shows an analogy between the surface-to-liquid heat and mass transfer in the gas-liquid, liquid-solid and gas-liquid-solid fluidized systems.…”
Section: Confirmation Of Presence Of Analogy Between the Heat And Massupporting
confidence: 89%
See 3 more Smart Citations
“…It is shown that the mass transfer correlation proposed by Yasunishi et al [26] is pretty close to the present correlation for the heat transfer, Eq. (12), which, in turn, shows an analogy between the surface-to-liquid heat and mass transfer in the gas-liquid, liquid-solid and gas-liquid-solid fluidized systems.…”
Section: Confirmation Of Presence Of Analogy Between the Heat And Massupporting
confidence: 89%
“…10 shows the plot of the quantity, Sh/Sc ±1/3 versus the specific power group, E 1/3 /D 4/3 /m l ±1 on the log-log coordinates for the mass transfer coefficient data for the immersed vertical cylinder or the wall in the three-phase fluidized bed [3]. The correlation for the mass transfer coefficient (solid line) is shown to be very similar to the correlation for the wall-to-bed mass transfer coefficient (broken line) by Yasunishi et al [26]. The heat transfer correlation (dotted line) in the present study (Eq.…”
Section: Confirmation Of Presence Of Analogy Between the Heat And Massupporting
confidence: 62%
See 2 more Smart Citations
“…Three-phase fluidization [1][2][3][4][5][6][7] is considered to be one of the vital methods of multiphase flow contacting operation because many fold improvement in heat and mass transfer coefficients is observed in it in comparison with two-phase and homogeneous flow systems in general. Further, it provides intimate mixing, isothermal conditions, uniform concentrations, high heat and mass transfer rates, high liquid holdup, ability to use small catalyst particles, accurate temperature control to achieve good selectivity and increased protection of catalyst, etc.…”
Section: Introductionmentioning
confidence: 99%